Disability Rating Scales in Parkinson's Disease: Critique and Recommendations. Issue 10 (6th October 2016) - Shulman, Lisa M.; Armstrong, Melissa; Ellis, Terry; Gruber‐Baldini, Ann; Horak, Fay; Nieuwboer, Alice; Parashos, Sotirios; Post, Bart; Rogers, Mark; Siderowf, Andrew; Goetz, Christopher G.; Schrag, Anette; et al.
ABSTRACT: Introduction: PD is associated with impairments that progress over time to disability. A large number of disability scales exist with little information on the best choice in PD. Methods: Following methodology adopted by the International Parkinson and Movement Disorder Society Task Force, a review of disability scales used in PD was completed. Based on prespecified criteria, the review categorized scales into: "Recommended"; "Recommended with Further Validation in PD Required" when well‐validated scales have not been specifically tested for clinimetric properties in PD; "Suggested"; and "Listed." Results: Twenty‐nine disability instruments were identified with nine scales fulfilling criteria for "Recommended" and 7 "Recommended with Further Validation in PD Required." Eight scales are "Suggested" and five scales are "Listed" for use in PD. The nine Recommended scales (Functional Status Questionnaire, Lawton‐Brody Activities of Daily Living, Nottingham Activities of Daily Living, Schwab and England Activities of Daily Living, Self‐Assessment PD Disability, Short Parkinson's Evaluation Scale/Scales for Outcomes in PD, Unified PD Rating Scale–II: Activities of Daily Living, Movement Disorders Society UPDRS Motor Experiences of Daily Living, PROMIS ® and Neuro‐QoL Physical Function), and the seven Recommended with Further Validation in PD Required are reviewed. Conclusion: Many disability measures are available and recommended for application in PD. The Task Force does not recommend the development of a new scale. Selection of the most appropriate instrument for a particular objective requires consideration of the characteristics of each scale and the goals of the assessment. © 2016 International Parkinson and Movement Disorder Society